The Effect of Pre-Milling Treatments on Functional and Rheological Properties of Brachystagia eurycoma (Achi) Seed Flour and Gum - Iwuamadi, Adaobi Chimuanya; Ugwuona, Fabian Uchenna; Iwuamadi, Ojiugo Chizoba (Direct Research Journal of Agriculture and Food Science, 2024)
Brachystegia eurycoma has good gelation properties which can impact a gummy texture when used in soups. The aim of this study is to explore the effect of pre-milling treatments on the functional and rheological properties of B. eurycoma seed flour and gum which will enhance the knowledge on utilizing Achi as a versatile ingredient in various food products. This study evaluates the effect of pre-milling treatments on the functional and rheological properties of B. eurycoma (achi) seed flours and gums. Batches (1kg) of B. eurycoma (Achi) seeds were subjected to four different pre-milling treatments (soaking, boiling, toasting, and fermentation) at various time intervals followed by processing steps to obtain fine flour and gum samples. Locust bean flour and gum were used as control. The results from the different pre-milling treatments of B. eurycoma seed flours and gum showed that the wettability of the flour and gum samples were high and rapid which ranged from 35.33±0.58s to327.33±6.43s and 46.67±1.06s to 99.67±2.08 respectively, hence it tends to reduce clumping, ensuring efficient functionality. The Modulus of elasticity of B. eurycoma flours and gums were also high with a range of 75.47±0.00N/mm2 to 182.42±0.01N/mm2, this indicates a relatively incompressible fluid. Gums from seeds boiled for 30min and 45min had the highest emulsion capacity, foaming capacity and wettability (B30 = 72.87%, B45 = 76.50%; B30 = 23.83%, B45 = 27.40% and B30= 91.33 s, B45= 99.67 s respectively), hence, can be said to be the best gum with high stability for commercial purposes. Gum samples from seeds fermented for 18 hrs had low viscosity with high shear rate (44.66 NS/mm2 and 41.04 NS/mm2; 0.26S-1 and 0.28S-1) hence, can be said to show a pseudoplastic or shear thinning behavior of B. eurycoma gum. This will enhance the texture, mouth feel, stability and uniformity of the gums when incorporated into a food system. This study revealed that B. eurycoma flours and gums from different pre-milling treatments will be very useful for the large-scale manufacturers and consumers not just because it is economical but is also a natural additive.
Keywords: gums; Flours; soaking; boiling; toasting; fermentation